INVESTIGATION OF BANK FAILURES IN TURKEY VIA PANEL-SURVIVAL ANALYSIS (Third Sector Social Economic Review, 2021)
Developments in the banking sector are both affected by the international regulations and the economic structure of the country. In this respect, the analysis and interpretation of the banking sector is very important. In this study, the factors affecting the failure of banks are analyzed in terms of some financial ratios of banks. The panel-survival analysis method which is used for inferences, is a combination of panel data analysis and survival analysis methods. The risk factors on banks' ability to continue their activities under a risk factor that may change in time are analyzed with this method. 61 banks operating in Turkey and their published joint financial ratios for the period 2000-2019 are included in the analysis. According to the results, it is noteworthy that the bankruptcy risk of foreign banks is approximately 62% lower than domestic banks. In addition, according to the estimated model, it has been observed that high liquidity and asset ratios and low interest income structure can lead to reducing the bankruptcy risk.
Keywords: Banking; bankruptcy; survival analysis.